The main factors affecting the selection of courses related to food services among male students in vocational colleges - Tukiran, Nor Anis Intan Aqiah; Muhammad Diah, Nadiah (Penerbit UTHM, 2021)
The education system in Malaysia is divided into several types: technical and vocational education, general education and religious education (Rashid, 2006). The technical and vocational fields emphasize knowledge and skills as well as provide good employment opportunities to young people. While public education emphasizes on academic knowledge. Malaysia is a rapidly developing country and is aiming to become a developed nation by the year 2020. Industry engaged in food services is one of the growing segments of the Malaysian economy. Indirectly the growth and growth of the rising food service industry has created vast career opportunities for graduates. However, along with these developments, gender imbalances between male and female students in food services are often the main topic for debate.